Semantic Analysis of The Relation of The Meaning of The Words Human and Jinn in The Qur'an - Annisa, Maryam Nur; Usman, Mohamad Alil; Kiswanto, Dudi (Borneo Journal of Language and Education, 2023)
The purpose of this study was to uncover the meaning of the words human and jinn as well as the relation of meaning between the words human and jinn mentioned in the Qur'an. The words human and jinn are repeatedly mentioned in the Qur'an and are often found side by side. Of course, there is a connection of meaning between the two. The purpose of uncovering the relation of the meanings of the words "human" and "jinn" in the Qur'an is to gain a deeper understanding of the concept, nature, role, and interaction between the two entities in the Islamic view. The meaning in question includes an understanding of the conceptual aspects, roles, interactions, and implications of the relationship between humans and jinns. In verses dealing with jinns and humans, several meanings are found including interactions and influences between humans and jinns, differences in nature, trials and disturbances from jinns, and jinns' obedience and partiality towards God and human.The method used is library research and uses a semantic approach, which includes data collection and analysis from relevant journals and articles. This research begins by defining semantic studies, then analyzing the meaning of the words human and jinn and the relationship of meaning between the words human and jinn in the Qur'an. The results showed that in the Qur'an, Allah mentions that humans and jinns are His creatures that have different forms, but there is a relationship between the two. For example, the Qur'an relates how Prophet Sulaiman's kingdom was built with the help of jinns. In addition, there was also an incident where a group of jinns came to listen to the Qur'an reading from the prophet Muhammad SAW. In the Qur'an, it is affirmed that there are Muslim jinns and infidel jinns. Muslim jinns are jinns who obey Allah's comhumands, while infidel jinns are jinns who disobey Allah's comhumands. Although humans and jinns live in different dimensions, there will always be interactions between the two. Looking at this, according